Accounting fables : tales of race and racism in the borderlands of business - Lewis, Anton (Emerald Publishing Limited, 2025)
Blending both fact and fiction the tales in Accounting Fables repeatedly reiterates that race and racism are an enduring malevolence in accounting and commerce, because it is part of a society in which both race and racism are central tenets to existence. Accounting Fables utilizes the Critical Race Theory methodology of Counter storytelling, where the reader is immersed in a differing world view of what is meant by Black/White/Me and Other. Highlighting and interrogating what is and what can be understood of race and the business landscape in our troubled times and examining race and racism in accounting and business in the context of racial fairy tales, this compilation of revelatory race-centric fables is presented to inspire empathy and understanding for the centrality of race and racism in business today. Accounting Fables is a timely intervention when discrimination has become a universal topic of discussion once more, forcing people to question and re-evaluate its meaning and effect. People need a newer lens with which to revisit the fraught age-old problem of race particularly in the context of business. That is provided here.